The Formation Process of Ahmadiyya Movement - Şenol Zaman (Kader, 2023)
This thesis examines the life, ideas, and the formation process of the Ahmadiyya movement, focusing on Mirza Gulam Ahmed. The thesis consists of an introduction and three chapters. In the introduction, information is provided about the political, social, religious, and cultural structure of the Indian Subcontinent, where Mirza Gulam Ahmed was born, lived, and passed away. The religions, Islamic sects, and various political and social conditions in the Indian Subcontinent are analyzed. The first chapter of the study provides information about Mirza Ghulam Ahmad's birth, childhood, upbringing, marriages, and education, as well as the content of his works. It explores Gulam Ahmed’s charismatic leadership and the formation of the Ahmadiyya community's fundamental doctrines, including claims of being a Muhaddis (one who receives divine revelations), a Mujaddid (renewer of faith), the Promised Messiah, and the concept of the finality of prophethood. Additionally, the chapter delves into the belief of Kalki Avatar among the followers of the Ahmadiyya movement. The second chapter focuses on the period after Gulam Ahmed 's death when the leadership of the Ahmadiyya community passed to Hakim Nureddin in 1914. Following his death, the Ahmadiyya community split into two fractions: the Qadiani and Lahori groups. The reasons behind this division are explained in detail. In the third chapter, Mirza Ghulam Ahmad's debates with Islamic scholars, Arya Samaj groups, Christian missionaries, and priests are discussed, along with the reactions of these groups towards the Ahmadiyya movement. Gulam Ahmed emphasized the need for jihad to be conducted through "word" and "knowledge," asserting that the door of revelation had not been closed. His influential works, such as Berahin-i Ahmadiyya (The Proofs of the Ahmadiyya Movement), Tevzih-i Meram (Explanation of the Objectives), and Izala-e Evham (Removal of Doubts), played a significant role in disseminating his ideas. His dreams were compiled in the book titled "Tezkire."